A review on intrathecal administration of medications for leptomeningeal metastases in solid tumors - Wang, Xuemei; Yao, Chi; Quan, Li; Zhou, Junxiang (Frontiers in Pharmacology, 2025)
Leptomeningeal disease (LMD) is a particular mode of central metastasis in malignant tumors. It occurs when tumor cells infiltrate the subarachnoid space and cerebrospinal fluid (CSF), spreading throughout the central nervous system (CNS). LMD is a rare but devastating complication of malignant tumors. It can occur in various types of cancers, with lung and breast cancer being the most frequently associated. The treatment approach for LMD includes a combination of supportive care, surgery, chemotherapy, radiotherapy, targeted therapy, immunotherapy, and intrathecal (IT) therapy, among other modalities. Despite the challenges in determining the optimal treatment for LMD, IT therapy remains one of the primary therapeutic strategies. This therapy can directly circumvent the blood–brain barrier. Moreover, a low-dose medication can achieve a higher drug concentration in the CSF, resulting in better cytotoxic effects. Chemotherapy drugs such as methotrexate, cytarabine, and thiotepa have been widely studied as traditional IT therapies. In recent years, the advent of novel anti-tumor drugs has led to a growing number of agents being employed for IT administration in the treatment of malignant tumors with LMD. This article presents a comprehensive review of the current advancements in IT administration of chemotherapy, targeted, and immunotherapy drugs for the treatment of LMD in solid tumors. In addition, we also discuss the safety issues associated with IT therapy, summarize the advantages of IT administration of different types of anti-tumor drugs, and put forward some suggestions for reducing adverse reactions. It is hoped that future research will focus on exploring more potentially effective anti-tumor drugs for IT treatment, conducting in-depth pharmacokinetic studies, and developing long-acting and low-toxic IT administration regimens for the treatment of meningeal metastases.